EFISIENSI PENGGUNAAN TEMPAT TIDUR PADA PELAYANAN RAWAT INAP TAHUN 2024 DI RUMAH SAKIT AWAL BROS GAJAH MADA TANGGAL 20 JANUARI S/D 05 FEBRUARI 2025 - Mirawati, Dian; SITUMORANG, MASRIANI; Dr.Mulyana, SKM., M.Kes; ERWINDA, TASYA AULIA; DELIA ALTESA PUTRI; SULIS OKTA ANGGERAINI (Journal of Hospital Administration and Management (JHAM), 2025)
Hospital bed utilization efficiency is an essential indicator used to assess the performance and service quality of inpatient care. This study evaluates the efficiency of bed use at Awal Bros Gajah Mada Hospital in 2024 using the Barber Johnson method, which incorporates four core indicators: Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), and Bed Turn Over (BTO). Data were obtained from inpatient daily census reports, totaling 57,729 hospitalization days, 261 available beds, and 19,432 discharged patients. Results showed that AvLOS, TOI, and BTO met the ideal standards of Barber Johnson, while BOR remained below the optimal range. The analysis also identified incomplete daily census documentation as the main constraint in producing accurate indicators. Factors contributing to census inaccuracy included high nurse workload and limited understanding of reporting procedures. This study concludes that although most indicators reflect efficient bed utilization, improvements in BOR and census accuracy are still required to optimize hospital resource management.